2023
DOI: 10.18280/mmep.100110
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Machine Learning Based Identification of Adult Epilepsy

Abstract: Epilepsy is a chronic non-communicable illness that affects brain individuals and impacts more than 50 million people globally. To predict epileptic seizures, we proposed machine learning-based ensemble learning technique in this study. In the preprocessed stage, we applied some important techniques such as Power line noise reduction and dividing the record into windows of 5 seconds. The project is created by the help of ensemble machine learning technique, which employs several machine learning algorithms, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In that research, we suggested an electronic data exchange (EDI) framework for smart healthcare in the context of smart cities supported by blockchain technology. To enable secure and effective EHR maintenance and exchange among multiple entities in the smart healthcare ecosystem, the proposed platform makes use of the benefits of blockchain technology [56][57][58][59][60]. Four essential parts made up the proposed framework: (1) Personal servers are local storage devices that store and encrypt EHR and communicate with cloud servers.…”
Section: Discussionmentioning
confidence: 99%
“…In that research, we suggested an electronic data exchange (EDI) framework for smart healthcare in the context of smart cities supported by blockchain technology. To enable secure and effective EHR maintenance and exchange among multiple entities in the smart healthcare ecosystem, the proposed platform makes use of the benefits of blockchain technology [56][57][58][59][60]. Four essential parts made up the proposed framework: (1) Personal servers are local storage devices that store and encrypt EHR and communicate with cloud servers.…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, the inconsistency of these signals due to varying physiological and psychological conditions points out the reliability problem of EEG signals under different motor/mental tasks. Besides, the large data size of EEG signals is another problem [93] for cognitive systems. Therefore, a Cube-Code methodology is proposed to overcome these problems in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The Euclidean distance is the unit of measurement used by the K-Means method to determine the distance between an object and the centroid. The process goes on until there is no net change left [43][44][45][46]. Figure 6 presents the clustering plot using a simple K-Means algorithm.…”
Section: Simple K-meansmentioning
confidence: 99%